The Role of the Audit Committee regarding Non-Audited Information - Bender, Ruth (Cranfield University, 2007)
The volume of non-audited information released by companies is extensive, and growing. This information has the power to move the share price. However, there are few regulations concerning this information, and practices differ widely. The tone of such information is often as important as the underlying content. A hierarchy of oversight is necessary. Not all of the information disclosed should or could be reviewed by non executives. Companies have to determine the significance of each statement and judge whether it is a matter for Board review, for delegation to the audit committee, or for the executive management. The Board should confirm that appropriate processes are in place to ensure the probity of the disclosures. Narrative disclosures in the financial statements are generally reviewed in some detail by the Board and the audit committee. The preliminary statement of results is reviewed by either the Board or the audit committee, or both. Particular attention is paid to the tone and outlook of this document. The level of review of interim statements by audit committees varies between companies. The level of audit committee or non executive involvement in the pre-close statement also differs significantly between companies. Practices regarding investor/analyst presentations vary. In a few companies the non executives see both the slides and the scripts for the presentation before the event, and have the time to make comments. However, in a significant number of organisations there is little non executive input or review. This was seen as a matter for some concern. It was felt that it would be useful for there to be broad guidelines concerning what is expected with regard to the non-audited information in investor/ analyst presentations and in the pre-close statement. This would be of use to non executives and also to finance directors. However, it would be inappropriate for standards or regulations to be introduced in this area.